The Impact of Promotion, Product Quality, and Trust toward Online Impulsive Buying Decisions: The Mediating Role of Flow Experience - Mutia Nurlaili; Ririn Wulandari (Sultan Publisher, 2024)
Online purchasing has experienced significant growth, with approximately 40 percent of total online purchases classified as impulsive. However, there is a gap between the potential rise in online purchases and the proportion of impulsive purchases, which remains at 40 percent. To address this gap and boost short-term sales for producers, this study aims to evaluate the impact of promotion, product quality, and trust on online impulsive buying decisions, considering the role of flow experience as an intervening variable. The research employs a descriptive quantitative method, collecting data through questionnaires using a Likert scale. The study was conducted in the D.K.I Jakarta area, involving 246 respondents. Data analysis was performed using path analysis to examine the relationships between the independent variables (promotion, product quality, and trust), the intervening variable (flow experience), and the dependent variable (online impulsive buying decisions). The findings reveal that promotion has a positive and significant influence on online impulsive buying decisions. Moreover, promotion significantly impacts flow experience, which in turn mediates the effect of promotion on online impulsive buying decisions. On the contrary, product quality and trust do not significantly affect either online impulsive buying decisions or flow experience. This suggests that promotional activities are crucial for enhancing impulsive purchases online, while product quality and trust play a lesser role in this context.